Sistem Pengendalian Intern Dalam Pemberian Kredit Usaha Masyarakat di Badan Usaha Milik Desa (BUMDES) Tirta Rahayu Desa Yeh Sumbul, Kecamatan Mendoyo, Kabupaten Jembrana - Yahya, Andi; Suwena, Kadek Rai (Universitas Pendidikan Ganesha, 2021)
The purpose of this study was to determine the internal control system in providing community business credit at Tirta Rahayu Village-Owned Enterprises (BUMDES) and to find out the problems faced by Tirta Rahayu Village-Owned Enterprises (BUMDES) in implementing the credit-giving internal control system. This type of research is descriptive qualitative. The research location in this study is the Village-Owned Enterprises (BUMDES) Yeh Sumbul Village, Mendoyo District, Jembrana Regency. The subjects in this study were the Head of BUMDES Tirta Rahayu Yeh Sumbul Village, the BUMDES Secretary Tirta Rahayu Yeh Sumbul Village and the BUMDES Supervisor Tirta Rahayu Yeh Sumbul Village. The object of this research is the internal control system in providing community business credit in BUMDES Yeh Sumbul Village. The data collection method used the observation and interview methods, the observation method was used for direct observation to the location of the Tirta Rahayu Village Owned Enterprise, Yeh Sumbul Village. In general, the internal control system at BUMDES Tirta Rahayu Yeh Sumbul Village has been implemented in accordance with applicable rules. The problems faced by BUMDES Tirta Rahayu in Implementing the Internal Control System for Providing Credit are inadequate human resources, HR owned by BUMDES Tirta Rahayu is still lacking because the number of employees is too few and the quality of education is low besides that the management's discipline in carrying out their duties is deemed not good, so that in carrying out the task often takes a long time.Keywords: Internal Control System; Business Credit; BUMDES